Prehabilitation in preparing patients with inflammatory bowel diseases for surgery, including nutritional treatment and psychological support - Stanisław Głuszek; Martyna Głuszek-Osuch; Dorota Kozieł; Jarosław Matykiewicz (Studia Medyczne, 2023)
Despite progress in the pharmacological treatment of inflammatory bowel diseases (IBD), surgery is still an integral part of the treatment of ulcerative colitis and Crohn’s disease. The probability of adverse effects of the procedure in this group of patients is related to the specificity of IBD and depends on modifiable and non-modifiable risk factors. Optimization of health must therefore rely on a multi-directional and individualized approach to a patient. Proper preparation of the patient for surgery consisting in nutritional and psychological support, improvement of physical efficiency and encouragement to give up addictions can bring a real benefit in improving the treatment results. The paper discusses the principles, benefits and limitations of the use of elements of prehabilitation in the surgical treatment of patients with IBD.